2014
DOI: 10.1016/j.jssc.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaX (X=I or Cl) additions on GeS2–Ga2S3 based glasses

Abstract: a b s t r a c tChalcogenide glasses in the pseudo-ternary system NaX-GeS 2 -Ga 2 S 3 (X¼ Cl or I) were synthesized. Different series were investigated in order to highlight the influence of the sodium halide addition on two different host glasses (GeS 2 ) 80 (Ga 2 S 3 ) 20 and (GeS 2 ) 72 (Ga 2 S 3 ) 28 . Macroscopic properties including density and characteristic temperatures, such as glass transition temperatures T g and crystallization temperature T x , were determined for a maximum molar content of NaX equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
6
10
0
Order By: Relevance
“…In this article, we report a systematical study on Na‐ion conduction behavior of glasses and GCs in GeSe 2 –Ga 2 Se 3 ‐NaI system. Similar study has been conducted on sulfide glasses of GeS 2 –Ga 2 S 3 –NaX (X = Cl or I), and a low IC of ~10 −8 S/cm was obtained at room temperature for the glasses with only 10 mol% NaX. In contrast, lithium IC is much larger (~10 −6 S/cm) for the glasses with the same compositions, suggesting that the network structure of sulfide glasses with small size of the sulfide anion units is more suitable for the transportation of Li + ions than that of Na + .…”
Section: Introductionsupporting
confidence: 71%
“…In this article, we report a systematical study on Na‐ion conduction behavior of glasses and GCs in GeSe 2 –Ga 2 Se 3 ‐NaI system. Similar study has been conducted on sulfide glasses of GeS 2 –Ga 2 S 3 –NaX (X = Cl or I), and a low IC of ~10 −8 S/cm was obtained at room temperature for the glasses with only 10 mol% NaX. In contrast, lithium IC is much larger (~10 −6 S/cm) for the glasses with the same compositions, suggesting that the network structure of sulfide glasses with small size of the sulfide anion units is more suitable for the transportation of Li + ions than that of Na + .…”
Section: Introductionsupporting
confidence: 71%
“…Not surprisingly, for each series, addition of LiCl leads to a decrease in T g , accompanied by a ∆T increase. The same phenomenon was observed in GeS 2 –Ga 2 S 3 system with insertion of NaCl or CsCl . This behavior happens consequently to the Cl introduction, breaking Ge–S and Ga–S bonds, and leading to a decrease in the glass network connectivity.…”
Section: Discussionmentioning
confidence: 46%
“…Moreover, it was reported that alkali halides (MX) could be incorporated to this glass matrix, without inducing drastic instability, especially at low or intermediate MX content in comparison with other systems. Among halides, alkali chloride glasses are easier to prepare and have a better atmospheric stability . Otherwise, addition of halogenide combined to charge carrier (e.g., Li + , Na + or Ag + ) is reported to induce a drastic increase in ionic conductivity, especially with Li halide, as shown in several studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the intensity of bands at 310 cm −1 and 340 cm −1 decreases gradually with the AgCl content from 0 to 55 mol% most probably due to the joint effects of Cl − and Ag + on the network structure of the glass. On one hand, Cl − ions can act as a glass network terminal to replace some bridging S to bond with As, leading to formation of the mixed Ag y As[S 3-y Cl y ] pyramids 33 . On the other, an increase in Ag content induces more Ag-S bonds which have the larger bond length (2.6 Å) than the substituted As-S bonds (2.3 Å), making glass network more open 34 .…”
Section: Resultsmentioning
confidence: 99%